1975
DOI: 10.1111/j.1600-0722.1975.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Listerine® on dental plaque and gingivitis

Abstract: abstract— The present study was performed in 10 adults in order to evaluate the effect of an antiseptic mouthrinse (Listerine®) on the rate of dental plaque formation and gingivitis development during a 2‐week period when all efforts towards active mechanical oral hygiene were withdrawn. The study was performed as a crossover study and was carried out during four consecutive 2‐week periods. During the first and third periods (preparatory periods) the participants were subjected to repeated professional tooth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
(2 reference statements)
1
20
0
Order By: Relevance
“…Short-term studies have shown plaque and gingivitis reduction averaging 35% (25) and long-term studies have shown plaque reduction between 13.8 and 56.3% and gingivitis reduction between 14 and 35.9% (26, 27). Possible adverse effects reported in the literature include a burning sensation, bitter taste and possible staining of teeth…”
Section: Antisepticsmentioning
confidence: 99%
“…Short-term studies have shown plaque and gingivitis reduction averaging 35% (25) and long-term studies have shown plaque reduction between 13.8 and 56.3% and gingivitis reduction between 14 and 35.9% (26, 27). Possible adverse effects reported in the literature include a burning sensation, bitter taste and possible staining of teeth…”
Section: Antisepticsmentioning
confidence: 99%
“…sential oils [12][13][14] and to demonstrate superiority to 0.05% CPC rinses. 15 This experimental gingivitis model is useful as a short-term model to determine efficacy of mouthrinse formulations and has been found to be consistent with six-month clinical trials results.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their low toxicity and antibacterial properties, phenolic compounds are used in antiseptics and disinfectants, but also in mouth rinse preparations. Short-and long-term clinical studies have indicated that the daily use of Listerine s (Pfizer AB, Täby, Sweden), a mouth rinse that contains different phenolics such as thymol, eucalyptol, menthol, and methyl salicylate, may retard plaque buildup and reduce gingivitis (Fornell et al 1975, Gordon et al 1985, Axelsson & Lindhe 1987, Mankodi et al 1987, Depaola et al 1989, Overholser et al 1990, Brecx et al 1992, Ross et al 1993. The effect of Listerine s on plaque was ascribed to its bactericidal properties that were documented in vitro as well as in vivo (Ross et al 1989, Jenkins et al 1994, DePaola et al 1996, Pan et al 2000.…”
mentioning
confidence: 99%